Effects on cows, calves, and vegetation of nitrogen fertilization and burning bluestem pastures annually - Berger, Loren Lynn; Schalles, R.R.; Harbers, L.H.; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Burning and fertilizing pastures were evaluated on six Bluestem pastures by comparing performances by spring-calving cows and calves. Two control pastures were not burned or fertilized, two pastures were burned, and two were burned and fertilized with 40 pounds of nitrogen an acre applied aerially. Average daily gains of the calves did not differ significantly among treatments. The burned, fertilized, pastures produced significantly higher gains per acre, as their increased forage supported heavier stocking rates.
Keywords: Beef; Cows; Calves; Fertilization; Bluestem